2022
DOI: 10.21608/jppp.2022.114871.1056
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Certain Entomopathogenic Bacteria, Fungi with Pesticides for Controlling Spodoptera littoralis

Abstract: This study was conducted to identify the susceptible stages of the cotton leafworm, Spodoptera littoralis to the entomopathogens fungus, Metarhizum anisopliae and bacterium, Pseudomonas aeuriginosa. The mortality percentages recorded after treatment of the 2 nd and 4 th instar larvae of S. littoralis with concentration 1×10 8 spore/ml of M. anisopliae were 84.28 and 75.71% after 5 days of treatment. While, LT50 were 0.81 and 1.93 days for 2 nd and 4 th instar larvae of S. littoralis, respectively. P. aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Lotfy et al (2016) observed positive influences on the 2 nd and 4 th instar larvae of S. littoralis treated with spores of M. anisopliae at different concentrations in laboratory conditions. In other studies, it was found that Metarhizium brunneum was very effective against S. littoralis and can be considered as a potential biological control agent against S. littoralis larvae (Funda and Yusuf, 2021;Eleawa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Lotfy et al (2016) observed positive influences on the 2 nd and 4 th instar larvae of S. littoralis treated with spores of M. anisopliae at different concentrations in laboratory conditions. In other studies, it was found that Metarhizium brunneum was very effective against S. littoralis and can be considered as a potential biological control agent against S. littoralis larvae (Funda and Yusuf, 2021;Eleawa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%